Negotiating Identity: The Impact of Cultural Displacement, Memory and Adaptation on Children in Haiti is My Home - Haminudin, Aileen Rihana; Ang, Angelo Gallardo; Sarijowan, Meicy Sabbathany; Sandova, Jeshelyn Enjelina (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2024)
This research analyzes